2006
DOI: 10.1100/tsw.2006.175
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neuropsychological Outcome in Preterm Twins

Abstract: Few long-term studies have yet described neuropsychological outcome in preterm twins. Our aim was to assess, by long-term evaluation, neuropsychological outcome in preterm twins in order to define a correct follow-up program. Our study was a cohort one, with an index and a comparison group. Neonatal medical records of all preterm newborns admitted to our centre between 1991 and 1997 were reviewed and selected patients were recalled. The sample population included two matched groups of children aged 6—12 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, as previous research has suggested, preterm birth and low birthweight are modest predictors of future behavioral problems, 4,5,16 even when an array of possibly confounding variables are controlled in a systematically ascertained sample.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, as previous research has suggested, preterm birth and low birthweight are modest predictors of future behavioral problems, 4,5,16 even when an array of possibly confounding variables are controlled in a systematically ascertained sample.…”
Section: Discussionmentioning
confidence: 75%
“…For example, Nigg and Breslau 4 found evidence indicating a relationship between low birthweight (≤ 2500g) and ADHD based on teacher report at ages 6 and 11 years, as well as a robust effect of maternal smoking on ODD and CD. Furthermore, Iannone et al 5 found more negative neuropsychological outcomes as determined by assessments of learning and language difficulties in low birthweight (≤ 2500g) infants. In contrast, Goodman and Stevenson 6 did not find perinatal adversity, qualified by birthweight and birth order, associated with hyperactivity, and Miller et al 7 found no relationship between low birthweight (500–999g) and future behavioral difficulties at ages 5 and 8 years.…”
mentioning
confidence: 99%
“…Few long-term studies on multiple births separately consider children born prematurely. A recent study 44 compared a cohort of 6-to 12-year-old twins born between 27 and 36 weeks with a control group of singletons of the same age and born at the same GA and found that the twins had a higher risk of minimal brain dysfunction. In another study 45 of 2-year-old children born before 31 weeks' GA, no significant difference in the incidence of death or severe disability was observed between twins and singletons.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%